Acetylation in the regulation of autophagy. Issue 2 (1st February 2023) - Xu, Yinfeng; Wan, Wei
ABSTRACT: Post-translational modifications, such as phosphorylation, ubiquitination and acetylation, play crucial roles in the regulation of autophagy. Acetylation has emerged as an important regulatory mechanism for autophagy. Acetylation regulates autophagy initiation and autophagosome formation by targeting core components of the ULK1 complex, the BECN1-PIK3C3 complex, and the LC3 lipidation system. Recent studies have shown that acetylation occurs on the key proteins participating in autophagic cargo assembly and autophagosome-lysosome fusion, such as SQSTM1/p62 and STX17. In addition, acetylation controls autophagy at the transcriptional level by targeting histones and the transcription factor TFEB. Here, we review the current knowledge on acetylation of autophagy proteins and their regulations and functions in the autophagy pathway with focus on recent findings. Abbreviations : ACAT1: acetyl-CoA acetyltransferase 1; ACSS2: acyl-CoA synthetase short chain family member 2; AMPK: AMP-activated protein kinase; ATG: autophagy-related; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; CCAR2/DBC1: cell cycle and apoptosis regulator 2; BECN1: beclin 1; CMA: chaperone-mediated autophagy; CREBBP/CBP: CREB binding protein; EP300/p300: E1A binding protein p300; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GSK3: glycogen synthase kinase 3; HDAC6: histone deacetylase 6; HSPA8/HSC70: heat shock protein family A (Hsp70) member 8; KAT2A/GCN5: lysine acetyltransferase 2A; KAT2B/PCAF: lysine acetyltransferase 2B; KAT5/TIP60: lysine acetyltransferase 5; KAT8/MOF: lysine acetyltransferase 8; LAMP2A: lysosomal associated membrane protein 2A; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NBR1: NBR1 autophagy cargo receptor; OPTN: optineurin; PD: Parkinson disease; PE: phosphatidylethanolamine; PIK3C3/VPS34: phosphatidylinositol 3-kinase catalytic subunit type 3; PKM2: pyruvate kinase M1/2; PtdIns3P: phosphatidylinositol-3-phosphate; PTM: post-translational modification; RB1CC1/FIP200: RB1 inducible coiled-coil 1; RUBCN/Rubicon: rubicon autophagy regulator; RUBCNL/Pacer: rubicon like autophagy enhancer; SIRT1: sirtuin 1; SNAP29: synaptosome associated protein 29; SNARE: soluble N-ethylamide-sensitive factor attachment protein receptor; SQSTM1/p62: sequestosome 1; STX17: syntaxin 17; TFEB: transcription factor EB; TP53/p53: tumor protein p53; TP53INP2/DOR: tumor protein p53 inducible nuclear protein 2; UBA: ubiquitin-associated; ULK1: unc-51 like autophagy activating kinase 1; VAMP8: vesicle associated membrane protein 8; WIPI2: WD repeat domain, phosphoinositide interacting 2.